Exploring the Status of Voiceless Labiovelar Fricative /ʍ/ in Contemporary American English - Walczak, Dominika (Research in Language, 2024)
The study attempts to investigate the current status of the voiceless labiovelar fricative /ʍ/ in American English with reference to selected sociolinguistic variables, such as age, regional background, formality of the speech and prestige. The study comprises 17 subjects and 34 recordings of their speech – two recordings of a different level of formality per each speaker. All of the analyzed recordings are available online. The analysis focuses on wh-words, such as e.g. why, while, whale or white. In the first part of the study, the number of wh-context words in each speech is juxtaposed with the actual production of the researched variable. The second part of the study concentrates on the comparison of the obtained qualitative data with selected social variables. The results of the study may not only broaden the understanding of the voiceless labiovelar fricative use in American English but may also have pedagogical implications to whether the variable should be included in the phonetic courses on American English.